Struktur und Handlung in Lernwerkstätten Hochschuldidaktische Räume zwischen Einschränkung und Ermöglichung - Baar, Robert; Feindt, Andreas; Trostmann, Sven (Lernen und Studieren in Lernwerkstätten. Impulse für Theorie und Praxis, 2019)
The title "Structure and Action in Learning Workshops - Higher Education Didactic Spaces between Restriction and Enabling", the fifth volume of the series "Learning and Studying in Learning Workshops" takes up the question of the relationship between structural conditions and concrete actions of actors in higher education learning workshops. Since the restructuring of universities and educational programs in the context of the Bologna reforms, studying has become more structured and formalized. In contrast, learning workshops continue to open up spaces for self-determined and self-regulated learning processes. What does this situation mean for the work in university learning workshops? This volume brings together a total of 24 contributions that explore this question with both theoretical and empirical support and discuss the relationship between structure and action in learning workshops.